PELATIHAN PEMBUATAN VIDEO OFFICIAL PEMANDIAN SUMBERINGIN UNTUK MENDUKUNG TERWUJUDNYA DESA WISATA DI DESA WRINGINSONGO, KEC. TUMPANG, KAB. MALANG - Agustina, Hiqma Nur; Anyassari, Nugrahaningtyas Fatma; Fauzia, Maya Rizki; Novitasari, Novitasari; Rahayu, Eka Listianing; Handayani, Tri Astuti (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Tourism village is a village that has various characteristics and uniqueness, and therefore designated as a tourist attraction. Tourist village is a form of community empowerment since the village is run and managed by local community. In addition, it also drives utilization of local resources and development of local businesses. Studies have shown the impact of tourism village toward the village economy since tourism is a substantial economic base for developing an area. Situated in Tumpang, Malang Regency, Wringinsongo village has a lot of potentials, namely agriculture, fisheries, creative industry and tourism. One of which is a natural swimming pond called Sumberingin. However, number of visitors are relatively low because very few people, particularly those living outside Tumpang, have heard about this attraction. With adequate promotion, Sumberingin swimming pond can be a major tourist attraction. Therefore, Polinema decided to conduct a training on video-making and editing for members of BUMDes Tirta Jaya Kreasi. The objective is to provide some assistance to promote Sumberingin swimming pond. The findings demonstrated that the training increased the participants’ knowledge and skills in video-making from several interesting angles.